A Selection of Artist and Theory Books on Today’s Complexity of the Photographic Gaze - Panayides, Omiros; Stylianou-Lambert, Theopisti (My University, 2020)
A Selection of Artist and Theory Books on the Modern-Day Complexity of the Photographic Gaze
SITUATION #203
Keywords: Visual Arts and Performing Art